GEOSPATIAL ANALYSIS OF INSECURITY AND ITS THREAT ON ROAD TRANSPORTATION IN KADUNA STATE NIGERIA - Usman, Jibrin Gani; Ogbole, J. E. (FUDMA Journal of Sciences, 2023)
The escalating waves of criminal activities involving motorists and other road users on highways is alarming, consequently resulting in many travellers losing lives and properties. This paper is aimed at analyzing the spatial distribution of criminal activities and its threat on road transportation across the state. The study utilized both primary and secondary data sources namely: structured questionnaire (likert scale), FGD and printed material such as journals and records from security agency. The ArcGIS software was used to determine the spatial pattern of the criminal activities in the study area. The questionnaire was analyzed using Microsoft Excel Package and the results were presented in charts. The results indicated that the state is bedeviled with four major types of insecurities which are arm robbery, Kidnapping, Ethnic violence and religious violence of which armed robbery predominate with 32%. The results also indicated that more than 61% of the LGAs in state had faced at least one attacked for the period 2017 to 2021. The areas bothering thick forests such as Birnin Gwari, Chikun and Giwa Local Government Areas were heavily hit by criminal activities. It was recommended that security apparatus should be placed more on the problematic areas for proactive majors to minimize the incidences of the attacks.